PENGARUH SUMBER INFORMASI TERHADAP KEPUTUSAN ADOPSI INOVASI PERTANIAN BIOINDUSTRI SERAI WANGI- TERNAK - Rushendi Rushendi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
The innovation of bioindustry agriculture is expected to improve the knowledge, attitudes and skills of farmers through the information sources that will ultimately increase the incomes and welfare of the farmers. The application of technological innovation by farmers is affected by factor of individual potential in implementing innovation, the role of information sources in providing and disseminating innovation, and also external factors which allow the users to apply technological innovation.  The application of innovation  is also determined by the nature of the innovation  itself. The availability of information,  the credibility  of information  sources  and the means  of access to information  will determine the effect of innovation adoption decision. The purpose of this study is to find out the effect of information sources obtained by farmers on innovation adoption decision of bioindustry agriculture of citronella - cattle.  The study  used survey  method  with descriptive  quantitative  approach  with ,regression correlation test. The locations of study were selected purposively with cluster random sampling technique in 4 hamlets of Cikahuripan Village in Lembang District, in March-May 2016, with the num ber of farmers was 230. The results showed that the components of innovation adopted by farmers are cultivation of citronella, utilization of livestock waste into organic fertilizer, utilization of livestock waste into biogas for households, and production of yoghurt. Factors affecting innovation adoption decision of bioindustry agriculture of itronella- cattle are communication through dialogue, the validity of information and the competence level of informants.